Study of medical report on justice examination result at Dr. Sardjito Hospital - Beta Ahlam Gizela, Beta Ahlam Gizela (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2004)
Background: Every human violation or crime case, in which there is human as a victim needs medical proofing, namely the Medical Report for justice or Visum et Repertum in Indonesia. We also have an obligation in keeping medical confidentiality in medical practice. It is therefore, necessary to study relevance regulation of examination and disclosing medical confidentiality for justice.Objectives: The purpose of this study is to analyse management of Visum et Repertum of life person at Sardjito Hospital Yogyakarta.Methods: Visum et Repertum of life person at Medical Record Department of Sardjito Hospital was reviewed. The MEG protocol for examination and reporting from International Amnesty used as a standard. Results: The study shows that management of Visum et Repertum of life person at Sardjito Hospital was administratively inappropiate. There were some discrepancies between regulation and practice. There is no agreement between each doctors in managing cases. Generally, Visum et Repertum was accepted in content, but for the future an improvement is needed as International Amnesty.Conclusions: Management of life person cases for Visum et Repertum at Sardjito Hospital do not international standard.Key words: visum et repertum - living person - medical confidentiality - informed consent